Managing effectively in Academia a guide to good practice for academic managers and leaders in higher education - Wilkinson, Graeme (Sunway shorts, 2021)
This books provides a compact guide to good management practice in contemporary higher education. It covers key topics in day to day in academic management including managings academic staff, handling students as customers, thinking and acting entrepreneurially and strategically, and dealing with some of the most challenging issues faced by academic managers in 21st century universities. It is aimed at academic managers at all levels, from research group leaders and programme leaders to department heads and deans. It should be especially relevant to those who have been newly promoted into such roles. It will also be of value to those aiming ultimately for the most senior roles as provosts, presidents, and vice-chancellors.